Pendampingan Belajar Dasar Berhitung bagi Siswa SD di Mata Jemaat Ebenhaezer Mabu Alor - Landerius Maro; Lekison Padafani (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The outbreak of COVID 19 has resulted in educational institutions implementing an online learning system and the impact on students' declining abilities in mathematics. This service activity aims to help students understand the material about the basics of counting outside of school hours. This service activity was carried out at the Ebenhaezer Mabu Congregation, Alor Regency with the target of junior high school students in the area. This activity was carried out for 6 meetings, starting with the pretest and ending with the posttest. This activity is said to be successful because of the positive response from students and parents to this activity and an increase in scores between the pretest and posttest.